2011
DOI: 10.1111/j.1365-2036.2011.04901.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of gastro‐oesophageal reflux disease over 5 years under routine medical care – the ProGERD study

Abstract: SUMMARY BackgroundThe evolution of gastro-oesophageal reflux disease (GERD) under current management options remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 35 publications
4
50
0
10
Order By: Relevance
“…2,3 It is notable that their finding a higher 3-year mortality in patients admitted as an emergency and patients treated medically, rather than surgically, is consistent with studies of admissions for CD in the late 1990's, particularly with regard to the elderly.…”
Section: Mortality In Patients Hospitalised With Crohn's Diseasesupporting
confidence: 68%
See 2 more Smart Citations
“…2,3 It is notable that their finding a higher 3-year mortality in patients admitted as an emergency and patients treated medically, rather than surgically, is consistent with studies of admissions for CD in the late 1990's, particularly with regard to the elderly.…”
Section: Mortality In Patients Hospitalised With Crohn's Diseasesupporting
confidence: 68%
“…2,3 It is notable that their finding a higher 3-year mortality in patients admitted as an emergency and patients treated medically, rather than surgically, is consistent with studies of admissions for CD in the late 1990's, particularly with regard to the elderly. 4,5 Furthermore, their finding that surgery delayed >7 days from admission was associated with increased 3-year mortality, might support a case for earlier surgical intervention.…”
Section: Mortality In Patients Hospitalised With Crohn's Diseasesupporting
confidence: 68%
See 1 more Smart Citation
“…Despite medical therapy, in some patients disease may progress and lead to serious complications, such as volume regurgitation with aspiration and Barrett's metaplasia, a precursor to adenocarcinoma. The recently updated results of the ProGERD study, a large European open cohort multicenter study, showed that 9.7% of patients with GERD under routine medical care progress to Barrett's esophagus at 5 years of follow up [Malfertheiner et al 2012]. Potential risks associated with PPIs include B12 vitamin deficiency, Clostridium difficile infection, community-acquired pneumonia, hip fractures, and osteoporosis [Katz et al 2012].…”
Section: Comparison Of Current Therapeutic Options For Gastroesophagementioning
confidence: 99%
“…In previous studies, the progression rate from mild to severe is around 10% (6%-12.5%), although most studies were retrospective (31)(32)(33)(34)(35)(36)(37). In a prospective multicenter open cohort study, most GERD patients remained stable or improved over a 5-year observation period under current routine clinical care (38). Among those subjects, 10%-81% had unchanged symptoms and 19%-84% had reverted to normal or regressed.…”
Section: Discussionmentioning
confidence: 99%